2008
DOI: 10.2214/ajr.07.3565
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-Enhanced Sonography of Adrenal Masses: Differentiation of Adenomas and Nonadenomatous Lesions

Abstract: Contrast-enhanced sonography can be used to differentiate adenomas and nonadenomatous lesions with a sensitivity comparable with that of CT and MRI and may be a cost-effective method for preselection of patients with adrenal masses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 26 publications
1
28
0
3
Order By: Relevance
“…The adrenal glands are usually uniformly hypoechoic on ultrasound scans, and they are sometimes difficult to distinguish from vascular structures in the region without Doppler ultrasonography. 27 It is not unusual for the size and shape of the adrenal glands to vary from this general description. The phrenicoabdominal artery passes dorsal to and the phrenicoabdominal vein ventral to each adrenal gland (see Figures 15-2, C, E, and G).…”
Section: Normal Anatomy and Ultrasound Appearancementioning
confidence: 95%
See 1 more Smart Citation
“…The adrenal glands are usually uniformly hypoechoic on ultrasound scans, and they are sometimes difficult to distinguish from vascular structures in the region without Doppler ultrasonography. 27 It is not unusual for the size and shape of the adrenal glands to vary from this general description. The phrenicoabdominal artery passes dorsal to and the phrenicoabdominal vein ventral to each adrenal gland (see Figures 15-2, C, E, and G).…”
Section: Normal Anatomy and Ultrasound Appearancementioning
confidence: 95%
“…However, other types of tumors also occur. 27,45,57 Mineralization is less common with pheochromocytomas but may occur in approximately 10% of the cases. 38 A nodule or mass causing unilateral enlargement of the adrenal gland is usually identified (see Figures 15-9 and 15-10).…”
Section: Adrenal Gland Enlargement and Massesmentioning
confidence: 99%
“…Recent studies documented the use of the contrast-enhanced doppler sonography on characterization of adrenal masses (20,21). Friedrich-Rust et al found an early arterial contrast enhancement and rapid washout in all patients with primary and secondary malignant lesions of adrenal gland and in only 22 % of patients with benign adrenal masses at contrast-enhanced sonography.…”
Section: Diagnosismentioning
confidence: 99%
“…Friedrich-Rust et al found an early arterial contrast enhancement and rapid washout in all patients with primary and secondary malignant lesions of adrenal gland and in only 22 % of patients with benign adrenal masses at contrast-enhanced sonography. In the diagnosis of malignant adrenal mass, the sensitivity and specifi city of contrast-enhanced sonography were 100 % and 82 %, respectively (21). F FDG -PET is another method of distinguishing metastases from benign adrenal lesions.…”
Section: Diagnosismentioning
confidence: 99%
“…17). A study by Friedrich-Rust et al 72 showed that, on B-mode US, malignant lesions were significantly more heterogeneous in echotexture (71% vs 18%) and more hypervascular on Doppler images (57% of malignant lesion vs 7% of benign lesions). Another determinant of malignancy in their study was larger diameter of more than 4 cm with sensitivity and specificity of 71% and 79%, respectively.…”
Section: Incidentalomas On Ultrasoundmentioning
confidence: 99%